Product Characterization of Selected Dehydrated Vegetables (Carrots, Turkey Berries, Amaranth Leaves and Eggplant Leaves) - Ofori-Appiah, D. (University of Ghana, 2023)
Sub-Saharan Africa grapples with cyclical abundance and scarcity in agricultural produce due to seasonal weather patterns, leading to substantial post-harvest losses. In Ghana, approximately 40 50% of harvested crops go to waste, emphasizing the urgent need to enhance post-harvest processes, particularly for fruits and vegetables, aligning with the UN's strategic development goal 2 (SDG 2) for improved nutrition and food security. This study investigated the product characterics of dehydrated vegetables (amaranth leaves, eggplant leaves, carrots, and turkey berries). The research studied the impact of pre-treatments such as blanching and various drying methods (convection oven drying, solar drying, and freeze-drying) on different aspects of these vegetables. Steam blanching of carrots, amaranth leaves and egg plants for 5 minutes before drying stabilized the green colour (a*-values) of the dehydrated samples. On the other hand, hot water blanching of turkey berries for 1 or 3 minutes showed the least colour change from the control after drying. Drying was generally faster in blanched vegetables compared to unblanched vegetables. Drying kinetics varied and established thin-layer drying models, specifically, Page, Wang and Singh, and Lewis were identified as suitable for describing the drying characteristics. The study determined the phytochemical and nutraceutical composition of the dehydrated vegetables, to understand the influence of blanching and drying methods. This involved total phenolic content (Folin-Ciocalteu), total flavonoid content (aluminium chloride colorimetric assay), antioxidant activity (DPPH radical scavenging activity) using the UV Spectrophotometer. Lutein, β-carotene, catechins, chlorogenic acids and quercetin concentrations were measured using HPLC. Drying methods significantly (p<0.05) decreased the phytochemical content of the vegetables in this study. Blanching caused a reduction in the phytochemical content compared with the unblanched samples. Freeze-drying retained the highest amount of originally contained total flavonoids, DPPH inhibition, and total phenolics. The nutritional and anti-nutritional compositions were examined, emphasizing the impact of drying methods on proximate analysis, mineral content, and anti-nutrient levels. The dehydrated vegetables exhibited low moisture content and water activity, as well as low fat and crude fibre. The dehydrated vegetables contained essential minerals such as iron, zinc, potassium, calcium, magnesium, and manganese. Blanching was shown to reduce anti-nutrient levels, enhancing overall nutritional quality. Furthermore, the study assessed the sensory characterization and nutritional contribution of a composite vegetable powder from the selected vegetables. This highlighted an optimum formulation of approximately 33% amaranth leaves, 23% carrots, 27% turkey berries, and 17% eggplant leaves, through sensory evaluation. The optimum formulation (composite powder) was described as olive green, dry, gritty and herby. Lastly, the physico-chemical properties, microstructure, and storage stability of the composite vegetable powder were determined. The powder had a slight greenish-yellow colour with low water activity (aw) which ensures stability during storage. The composite powder showed favourable characteristics for convenient use in food preparations. Overall, these findings provide comprehensive insights into pre-treatment methods, preserving nutritional and sensory qualities, and developing composite vegetable powders to address nutritional deficiencies and enhance food preservation techniques.
PhD. Food Science
Keywords: Sub-Saharan Africa; Ghana; SDG